Consumo de bebidas álcoolicas e desfechos cardiometabólicos em duas coortes (ELSA-Brasil e PREDIMED-Plus) - Martinez, Oscar Geovanny Enriquez (2023)
The global consumption of alcoholic beverages has increased and is associated with cardiometabolic outcomes. It is important to investigate the effects of alcohol consumption, since the World Health Organization suggests that there is no safe level of consumption, although the results are conflicting. It has been reported that moderate consumption can bring benefits, especially for cardiovascular health. However, there are still gaps in knowledge about the true effect of alcohol consumption due to the lack of standardization of alcohol content, quantity of doses and type of drink, which can be beer, wine, or spirits. Therefore, the aim of this study is to investigate the relationship between alcohol consumption and cardiometabolic outcomes in two cohort studies, ELSA-Brasil and PREDIMED-Plus. The ELSA-Brasil is a cohort of active and retired employees of six institutions of both sexes and aged between 34 and 74 years. Belonging to Federal Universities of Bahia, Espírito Santo, Minas Gerais, Rio Grande do Sul, São Paulo and Oswaldo Cruz Foundation/ Rio in January. This study aims to investigate the incidence of chronic diseases in the adult Brazilian population, especially cardiovascular diseases, and type 2 diabetes. PREDIMED-Plus It is a randomized, multicenter clinical trial conducted by 20 higher education institutions in Spain with 6000 participants allocated into two groups intervention group (3000) and control group (3000), The recruitment period ran from September 5, 2013, to November 30, 2016, and the intervention has an average duration of 6 years, the expected average follow-up for clinical cardiovascular events will be 8 years. Participants are men aged 55 to 75 years and women aged 60 to 75 years, with BMI ≥27 and <40 kg/m2, who meet at least 3 criteria for metabolic syndrome, or cardiovascular risk. The results were written in three original articles The first manuscript aimed to evaluate the factors associated with HDL-C levels, with emphasis on Low HDL-C and extremely high HDL-C. The results showed that sociodemographic, anthropometric, lifestyle and health factors are related to HDL-C levels. Women, black individuals, the elderly, and alcohol consumers were less likely to have low HDL-C, while smokers, overweight individuals, inadequate waist-to-hip ratio, altered triglycerides and LDL- C were more likely to have low HDL-C. As for extremely high levels of HDL-C, the results showed a lower probability for smokers, overweight individuals, inadequate waist-to-hip ratio, altered triglycerides and LDL-C, and a greater probability for women, black individuals, the elderly and alcohol consumers. The second article focused on the association between excessive alcohol consumption and extremely high levels of HDL-C, finding a positive association OR CI 95% (1.92 1.4-2.5). And the third evaluated the association between alcohol consumption and cardiometabolic and anthropometric variables in two Brazilian (ELSA-Brasil) and Spanish (PREDIMED-Plus) populations: cross-sectional and longitudinal analysis. It was observed that the increase in alcohol consumption is associated with higher values of anthropometric and cardiovascular variables, such as body weight, β CI 95% (2.9 1.09-4.72), waist circumference β CI 95% (0.54 0.14-0.94), BMI β CI 95% (0.22 0.10-0.35), glucose β CI 95% (1.8 0.46-3.15), hemoglobin glycated β IC 95% (0.03 -0.01-0.07), total cholesterol β IC 95% (3.26 1.48-5.03), HDL cholesterol β IC 95% (0.12 -0 .35-0.58), LDL cholesterol β CI 95% (0.78 -0.80-2.36), triglycerides β CI 95% (12.21 8.45-15.9), systolic blood pressure β CI 95% (0.8 0.03-1.56) and diastolic β CI 95% (0.88 0.44-1.31). In addition, we observed that moderate and heavy drinkers are more likely to have 4 or 5 criteria of the metabolic syndrome. it is concluded that the consumption of alcoholic beverages has an effect on cardiometabolic variables regardless of the type and amount, showing different effects on health. These findings are supported by the fact that the analyzes were carried out on two different continents, and the results found were similar. However, it is important to emphasize that HDL-C levels must be analyzed with caution, since alcoholic beverages can increase these levels, and excessive consumption is more likely to reach extremely high levels, which is not positive. for cardiovascular health. These results have significant implications for clinical practice, as they can help health professionals to more effectively approach patients who consume alcoholic beverages.